Is a strict cow’s milk-free diet necessary to treat milk oral immunotherapy-related eosinophilic esophagitis? - Bianchi, Annamaria; Calvani, Mauro; Leonardi, Lucia; Remotti, Danilo; Paparella, Roberto (Acta Biomedica Atenei Parmensis, 2021)
We report the case of a 15-year-old boy who developed eosinophilic esophagitis (EoE) during cow’s milk oral immunotherapy (CM-OIT). In order to not completely invalidate OIT benefits, baked milk-containing foods were allowed instead of a strict CM-free diet. However, histological remission of EoE was reached only after a strict cow’s milk-free diet, not associated to pharmacological treatment. Nevertheless, given the limited data on real incidence of food OIT related EoE and potential beneficial treatment for this condition, we highlight the need of prospective studies aimed to evaluate if a strict CM free diet in OIT related EoE is always necessary to obtain remission of the disease or similarly to CM EoE, baked milk-containing foods” diet could be abeneficial treatment also in these patients.